Transcriptomic analysis reveals that methyl jasmonate confers salt tolerance in alfalfa by regulating antioxidant activity and ion homeostasis - Yin, YanLing; Yang, TianHui; Li, Shuang; Li, Xiaoning; Wang, Wei; Fan, ShuGao (Frontiers in Plant Science, 2023)
Alfalfa, a globally cultivated forage crop, faces significant challenges due to its vulnerability to salt stress. Jasmonates (JAs) play a pivotal role in modulating both plant growth and response to stressors. We showed that exogenous methyl jasmonate (MeJA) regulated alfalfa seed germination and primary root growth in a dose-dependent manner, with 5μM MeJA exerting the most efficient in enhancing salt tolerance. MeJA at this concentration elavated the salt tolerance of young alfalfa seedlings by refining plant growth, enhancing antioxidant capacity and ameliorating Na + overaccumulation. Subsequent transcriptomic analysis identified genes differentially regulated by MeJA+NaCl treatment and NaCl alone. PageMan analysis revealed several significantly enriched categories altered by MeJA+NaCl treatment, compared with NaCl treatment alone, including genes involved in secondary metabolism, glutathione-based redox regulation, cell cycle, transcription factors (TFs), and other signal transductions (such as calcium and ROS). Further weighted gene co-expression network analysis (WGCNA) uncovered that turquoise and yellow gene modules were tightly linked to antioxidant enzymes activity and ion content, respectively. Pyruvate decar-boxylase (PDC) and RNA demethylase (ALKBH10B) were identified as the most central hub genes in these two modules. Also, some TFs-hub genes were identified by WGCNA in these two modules highly positive-related to antioxidant enzymes activity and ion content. Thus, MeJA triggered a large-scale transcriptomic remodeling, which might be mediated by transcriptional regulation through TFs or posttranscriptional regulation through demethylation. Our findings contributed new perspectives for understanding the underneath mechanisms by which JA-mediated salt tolerance in alfalfa.